Acupuncture in human performance - Pelham, T. W.; Holt, L. E.; Stalker, R. (The Journal of Strength and Conditioning Research, 2001)
To this point in time, acupuncture has been used primarily as an analgesic, a therapeutic intervention that controls pain under pathological conditions. Although some of the mechanisms of acupuncture as it applies to pain relief have been studied, little is known of the positive and/or negative effects of this procedure on the physical performance parameters of healthy people, particularly highly trained athletes. After introducing acupuncture from historical and technique viewpoints, preliminary studies of the effects of acupuncture on strength, aerobic conditioning, flexibility, and sport performance are discussed, as well as concerns regarding the direction of research investigating the potential benefit and/or adverse effects of this practice. Finally, an argument is put forward for the establishment of guidelines for the use of acupuncture in the sports community.